MK‐6240 imaging features, cognitive associations in preclinical Alzheimer's disease and a case with imaging‐to‐postmortem correlates: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Betthauser, Tobey J.; Koscik, Rebecca L.; Jonaitis, Erin M.; Cody, Karly Alex; Erickson, Claire M; Mueller, Kimberly D.; Clark, Lindsay R.; Stone, Charles K; Christian, Bradley T.; Asthana, Sanjay; Salamat, Shahriar; Johnson, Sterling C.
Abstract: Background: Understanding imaging features and detection limits of tau PET tracers is crucial for making accurate inference about underlying tau pathology, including critical implications for clinical treatment and prevention trials. This study investigates imaging features of the tau PET tracer MK‐6240 and associations with preclinical cognitive decline and beta‐amyloid with an emphasis on elucidating the earliest detectable MK‐6240 signal. These findings are contextualized with the first report of imaging‐to‐postmortem correlates for MK‐6240. Methods: Participants recruited from the Wisconsin Registry for Alzheimer's Prevention underwent longitudinal cognitive assessment, and PiB and MK‐6240 PET imaging. Three regional MK‐6240 composites were generated based on MK‐6240 spatial correlations (MTL, cortical, visual cortex). Linear mixed‐effects models probed relationships between longitudinal cognitive trajectories (three‐test Preclinical Alzheimer's Cognitive Composite; PACC‐3), amyloid chronicity (estimated duration PiB(+) at baseline PACC‐3), and MK‐6240 in each composite region. MK‐6240 imaging outcomes were compared to neuropathological assessment for a 63 year‐old from the Wisconsin ADRC clinically diagnosed with early onset AD with PiB and MK‐6240 scans ∼2 months antemortem. Results: Inter‐regional MK‐6240 correlations indicated minimal spill‐in from extra‐axial signal for most brain regions with the lowest correlations observed in the MTL. Mixed‐effects models indicated a significant three‐way interaction between age, baseline amyloid chronicity and MK‐6240 SUVR on longitudinal PACC‐3 in all three composite regions. The three‐way interaction remained significant only in the MTL when excluding participants with Z(MK‐6240)>2 in the cortex or visual composite regions. Neuropathological assessment of the case with antemortem imaging indicated Thal phase 4 and Braak stage IV or V with grade 1 CAA. Asymmetry in the MTL and focal elevations were observed in MK‐6240 images in this case, but SUVR values were below regional cutoffs for tau positivity. Conclusions: Similar to reports with other tau tracers, MK‐6240 imaging‐to‐postmortem correlates suggest that tau‐related PET signal may not be detectable until later neuropathological NFT stages. The neuropathology results combined with the cognitive findings suggest that MK‐6240 signal in the MTL is indicative of more extensive tau pathology than can be observed with PET and thereby is disease‐related. Further work is underway characterizing the spatial correspondence between MK‐6240 and tau pathology.